TRADISI MEMBACA AL-QUR’AN: Kajian Living Quran Di Pondok Pesantren Tarbiyatunnasyiin Paculgowang Jombang - Zamzami, Arvin Krisna (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2022)
Education plays a crucial role in developing human resources, particularly in shaping intellectual capacity, skills, and moral character. In Islamic education, teachers hold a strategic position in cultivating students’ religious values, including fostering a culture of Qur’anic literacy. This study aims to analyze the role of Islamic Religious Education (PAI) teachers in developing a culture of Qur’an reading at SMP Tarbiyatunnasyiin Paculgowang Jombang, a formal school with a pesantren-based educational environment. This research employs a descriptive qualitative approach with a field study design. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that PAI teachers play a significant role in establishing a Qur’anic culture within the school environment. This role is manifested through strengthening students’ religious practices and moral values, implementing the 5S culture (smile, greeting, salutation, politeness, and courtesy), actively participating in religious events such as Isra’ Mi’raj and the Prophet’s Mawlid commemorations, and promoting Qur’anic literacy through collaboration with the Ummi Foundation Surabaya. Additionally, teachers regularly conduct tahsin sessions to standardize and improve their Qur’anic recitation before teaching students. These findings indicate that the integration of religious habituation, systematic Qur’an learning methods, and teachers’ exemplary roles contributes to the development of a Qur’an-reading culture as a form of Living Qur’an practice in the school context.